Neisseria elongata -mediated peritonitis in an end-stage renal disease patient on automated peritoneal dialysis, A case report and literature review. (December 2022) - Alsayed, Ahmed; Abdalla, El Mustafa; Ali, Bashir; Hatem, Ahmed; Albsheer, Khalid; Elhadi, Mohamed; Makawi, Amna
Abstract: Introduction: Peritoneal dialysis (PD) can result in peritonitis, which frequently causes severe and near-fatal clinical implications if left untreated. Usually, Gram-positive bacteria are the most common organisms involved. Uncommonly recognized as the cause of peritonitis in PD patients, Neisseria Elongata is a gram-negative nasal and oropharyngeal normal flora organism. Case presentation: We report a rare case of a 29-year-old man who had received automated peritoneal dialysis for six years and had Neisseria Elongata peritonitis. Discussion: Several case Reports of niseria-related peritonitis may point to the potential pathogenicity of such organisms and suggest that many cases of culture-negative peritonitis may have been misdiagnosed. Poor nutrition and chronic kidney disease have been suggested as potential risk factors for Neisseria elongata peritonitis [8], both of which are present in our patient. With appropriate antibiotic use, most of the cases respond well to empirical treatment. Conclusion: Although rare, Neisseria Elongata can lead to Peritoneal Dialysis catheter Peritonitis that, in some cases, require changing to hemodialysis. Highlights: Neisseria elongata can cause a wide range of Infectious manifestations including peritonitis. Peritoneal dialysis related peritonitis can be due to Neisseria. CKD and poor nutrition are important risk factors for Neisseria related peritonitis9. Most cases usually response well to appropriate antimicrobial therapy.